High Resolution and Labeling Free Studying the 3D Microstructure of the Pars Tensa-Annulus Unit of Mice - Wu, Jian-Ping; Yang, Xiaojie; Wang, Yilin; Swift, Ben; Adamson, Robert; Zheng, Yongchang; Zhang, Rongli; Zhong, Wen; Chen, Fangyi (Frontiers in Cell and Developmental Biology, 2021)
Hearing loss is a serious illness affecting people’s normal life enormously. The acoustic property of tympanic membranes plays an important role in the hearing capability of people, and it is highly dependent on the geometry, composition and microstructure of the tissue. The way that the tympanic membrane connects to the annulus also influences the sound conductivities and transmission of the tympanic membrane. While the conical geometry of the tympanic membrane is critical to the sound propagation in the auditory system, it presents significant challenges to the study of the 3D microstructure of the tympanic membrane using traditional 2D imaging techniques for comprehending its function. To date, most of our knowledge about the 3D microstructure and composition of tympanic membranes is built from studies using 2D microscopy, which precludes an accurate understanding of the 3D microstructure, acoustic behaviours and biology of the tissue. Although tympanic membranes have been reported to contain elastic fibres, the morphological characteristic of the elastic fibres and the spatial arrangement of the elastic fires with the predominant collagen fibres have not been shown in images. We have developed a 3D imaging technique for the three-dimensional examination of the microstructure of the full thickness of the tympanic membranes of mice without tissue dehydration and stain, and studied the 3D arrangement of the collagen and elastic fibrillar network with the capillaries and cells in the pars tensa-annulus unit at a close extension to the native. The most striking findings in the study are the discovery of the 3D form of the elastic and collagen network and close relationship of the elastic fibres with the elongated fibroblasts in the tympanic membranes. We have also showed the wall of the conical collagen and elastic scaffold present waveforms. Given the close relationship among the acoustic property, 3D microstructure and geometry of tympanic membranes, the findings will increase the understanding of the acoustic function of tympanic membranes and hearing mechanism. The knowledge will also be very helpful to the development of advanced cellular therapeutic technologies and 3D printing techniques to restore damaged tympanic membranes to the status close to the native.